Th1rteen r3asons why : a novel - Asher, Jay, 1975-; Razorbill (New York : Razorbill, 2007)
When high school student Clay Jenkins receives a box in the mail containing thirteen cassette tapes recorded by his classmate Hannah, who committed suicide, he spends a bewildering and heartbreaking night crisscrossing their town, listening to Hannah's voice recounting the events leading up to her death.
Yesterday one hour after school -- Cassette 1: side A -- Cassette 1: side B -- Cassette 2: side A -- Cassette 2: side B -- Cassette 3: side A -- Cassette 3: side B -- Cassette 4: side A -- Cassette 4: side B -- Cassette 5: side A -- Cassette 5: side B -- Cassette 6: side A -- Cassette 6: side B -- Cassette 7: side A -- Cassette 7: side B -- The next day after mailing the tapes.
550
Accelerated Reader/Renaissance Learning
AR
Keywords: Suicide -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Suicide -- Fiction; High schools -- Fiction; Schools -- Fiction; Interpersonal relations -- Fiction; Schools -- fiction; High schools; Interpersonal relations; Schools; Suicide; Suicide -- Fiction; Suicide -- Fiction; High schools -- Fiction; Interpersonal relations -- Fiction; Young adult fiction; Proofs (Printing); Young adult fiction; Proofs (Printing); Dust jackets (Bindings) -- 2007.; Young adult fiction; Fiction; Juvenile works; Young adult works; Psychological fiction; Suspense fiction; Young adult fiction; Miscellaneous fiction